The association of occupational noise exposure and the symptoms of hearing loss among construction workers in UiTM Puncak Alam / Mohd Zahiruddin Mohd Zahari - Mohd Zahari, Mohd Zahiruddin (2014)
Introduction: A study was conducted on the association of occupational noise exposure and the symptoms of hearing loss among construction workers in UiTM Puncak Alam, Selangor. The workers were selected from Machine Operators (n=29), In-Building Workers (n=17), and Outside Building workers (n=14). These workers were exposed to noise produced by the machines and construction activities.Methodology: A comparative cross sectional study was carried out where 60 questionnaires had been distributed among the Machine Operators (n=29), In-Building Workers (n= 17) and Outside Building Workers (n=14) in the construction site. Sound Level Meter and Noise Dosimeter were used to measure the area noise level and personal noise exposure level respectively.The noise exposure level among the workers showed there were a significant difference (p<0.05) of noise exposure level between the combinations of "Machine Operators and InBuilding workers" and "Machine Operators and Outside Building Workers". The association of symptoms of hearing loss between groups of Machine Operators, In-Building and Outside Building was analyzed by using Pearson chi-square test. There were no significance differences between three groups of workers experiencing Difficulty In Understanding Words since the p value was more than 0.05 (p > 0.05), meanwhile there is significant difference between three groups of workers experiencing TJ.Jrn Up Volume and Talking Loudly since the p values was less than 0.05 (p < 0.001 ).